Critical Review of Education Policy in North Sumatra Province: Real, Symbolic, and Rethoric - Sirozi, M; Siagian, Mhd. Darwis; Sumanti, Solihah Titin; Hamid, Fatimah (AL MURABBI, 2024)
This study critically examines education policy in North Sumatra Province (North Sumatra) by examining three dimensions: real, symbolic, and rhetorical. The real dimension refers to the implementation of policies on the ground, symbolically examines the meanings and messages contained in the policy, and rhetoric focuses on the discourse and narrative built around the policy. This research uses text analysis methods and in-depth interviews with various education stakeholders in North Sumatra. The findings of the study show that there is a gap between the ideal education policy and its reality in the field. Education policies are often hampered by a variety of factors, such as a lack of resources, complicated bureaucracy, and weak law enforcement. The symbolic dimension shows that education policies in North Sumatra are full of meanings and messages that aim to build a positive image of the government and legitimize power. However, this meaning and message is not always in harmony with the reality on the ground. The rhetorical dimension shows that the discourse and narrative built around education policy in North Sumatra are often bombastic and hyperbolic. This raises high expectations among the public, but it is not always met. This study concludes that education policies in North Sumatra need to be critically reviewed to ensure that they are truly effective, efficient, and fair. A strong commitment from the government and all stakeholders is needed to realize a quality and sustainable education policy in North Sumatra.